Implementation of the Pentahelix Model for Strengthening Blue Economy As Climate Change Mitigation in the Fishing Community of South Malang - Revaldo, Syahrul Helmi; Nurfirdaus, Revalin Aulia; Abbas, Era Astavia; Setiawan, Rizky Fajar; Sari, Wahida Kartika (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2026)
Climate change increases the vulnerability of coastal fishing communities, making strengthening the blue economy through collaborative governance crucial for enhancing resilience. This study analyzes the implementation of the Pentahelix model in strengthening the blue economy as a climate change mitigation strategy in the fishing communities of South Malang. An exploratory sequential mixed-methods design was used, combining qualitative data from in-depth interviews and observations with representatives of Pentahelix actors and quantitative analysis using the Analytical Hierarchy Process (AHP). Qualitative findings indicate that although the government, academics, business actors, the community, and the media have fulfilled their respective roles, collaboration remains fragmented due to limited coordination, inadequate stakeholder participation, and inadequate integration of research findings into policy formulation. The AHP analysis produced consistent results (CR = 1.00%), indicating reliable priority rankings. Socio-economic impacts emerged as the highest-priority criterion (27.14%), while sustainable marine tourism diversification was identified as the main strategic alternative (22.34%) with a consistent ratio (CR = 1.48%). This strategy is considered capable of diversifying fishermen's livelihoods, reducing dependence on capture fisheries, and increasing community resilience while preserving coastal ecosystems.